CORRELATION OF STOMATA DENSITY TO RUST SEVERITY ON SOME ACCESSIONS OF MAIZE GERMPLASM - ., Suriani; Djaenuddin, Nurasiah; Talanca, A.Haris (Universitas Lampung, 2018)
Correlation of stomata density to rust severity on some accessions of maize germplasm. Rust is an important disease on maize. Control of rust using resistant varieties is recommended because it is more practical and environmental friendly. This research aims to study on the correlation of stomata density to rust severity on the several maize germplasm accessions. The research was conducted in Bontobili Farm Experimental Station and ICERI Pathology Laboratory, held from March to August 2017; it used Randomized Block Design with 2 replicates. As much as 30 corn germplasm accessions and 2 varieties for comparison (Bima 10 and Anoman) were planted by spacing 20 x 70 cm. The inoculation of Puccinia sp. was allowed to occur naturally. Printing of stomata was conducted with painted the lower part of corn leaf with nail polish transparent. After drying, it was pasted with clear isolation and then it was pulled and saved on glass object. Observed parameters were rust severity on the age of 50, 60, 70 days after planting and density of stomata. Results of the experiment showed that disease severity of germplasm accession number 2, 218 and 243 were not significant with comparison (tolerant variety). Germplasm with accession number 234 was categorized tolerant to rust. The rust infection rate on all accession were categorized by mild to moderate. Density of stomata of each maize germplasm accession was significantly correlated with rust severity, the increase of stomata density could increase of rust severity at 0.73%.